Joglosemar in the investment vortex: Is inclusive growth just rhetoric? - Rina Manasika; Romanus Yoseph Kun Haribowo Purnomosidi (Universitas Sebelas Maret, 2025)
Doubling per capita income may create the illusion of progress, but it hides a more troubling fact by obscuring the underlying socio-economic challenges. As a national economic, strategic area (Kawasan Strategis Ekonomi-KSE) and the golden triangle in Central Java Province - Special Region of Yogyakarta, the achievement of inclusive economic growth in the cities of Yogyakarta, Surakarta, and Semarang remains a question. This study aims to analyze the role of investment in the leading sector in achieving inclusive economic growth in the Joglosemar reliable area. The objective was achieved using location quotient (LQ), shift share (SS), Klassen typology analysis methods, and path analysis. As a result, developing strategic projects and establishing Joglosemar’s main development area, which attracts investment in leading sectors, have not created inclusive economic growth. Foreign direct investment (FDI) or (penanaman modal asing-PMA) and domestic direct investment (DDI) or (penanaman modal dalam negeri-PMDN) partially do not have a significant effect on the inclusive economic growth of the Joglosemar reliable area through the leading sector. To strengthen the broad multiplier effect, the government can align fiscal and monetary policies with the needs of leading sector development. In addition, the government can also create a collaboration scheme between FDI and DDI to maximize the contribution of both as a source of investment.